576. ESOPHAGEAL ACHALASIA: VERY LONG FOLLOW-UP STUDY ON PATTERNS AND COMPLICATIONS OF POST MYOTOMY GERD. (24th September 2022) - Tassi, Valentina; Lugaresi, Marialuisa; Mattioli, Benedetta; Daddi, Niccolo'; Pilotti, Vladimiro; Mattioli, Sandro
Abstract: Since the adoption of the Heller myotomy, surgeons have modified the original technique to balance the cure of dysphagia and the consequent cardial incontinence. Surprisingly, today post POEM 30-50% erosive-ulcerative esophagitis rates are by some put inside normality. Our group had the opportunity to follow up methodically patients submitted to Heller myotomy since 1955. Aim is to provide information on long-term outcomes of Heller myotomy for esophageal achalasia with or without an antireflux fundoplication. In first instance 83 patients underwent a long abdominal myotomy (AM 1955-72), 30 patients a transthoracic myotomy according to Ellis (TM 1973-78), 364 patients the Heller-Dor operation with intraoperative manometry to calibrate myotomy, length and pressure of the Dor fundoplication (HD 1979-2021). Starting on 1973 these patients underwent a prospective follow-up program of timed lifelong clinical, radiological, endoscopic evaluations. Since 1973 an endoscopic-radiologic-clinical timed follow up has been established. GERD symptoms/esophagitis were evaluated. AM, TM and HD groups were followed up for a median period of 25, 27, 14 years respectively. GERD symptoms-esophagitis occurred in AM 29.5%-28.1%, TM 30%-30%, HD 6.6%-5.8%. Timing of esophagitis after HD revealed: early onset (6-24 months) in 8 (2.2%), late onset (25 months-14 years) in 13 (3.6%). PPIs controlled reflux symptoms (71%vs14%, p<0.0001) but not esophagitis (43%vs46%, p= 0.075). Among 50 patients with erosive/ulcerative reflux esophagitis, Barrett's esophagus was diagnosed in 21 (42%) at a median period of 112 months since myotomy. In this group low-grade dysplasia occurred in 12 (24%) and high grade dysplasia/adenocarcinoma in 5 (10%). After surgical Heller myotomy not associated with an efficient antireflux procedure, GERD occurred in 30% which decreased to 6% after HD. A Heller-Dor operation is a competitive option for the cure of esophageal achalasia if this operation is performed according to the rules of surgical physiology learned by means of intraoperative manometry. The adoption of POEM in alternative to HD for the treatment of achalasia should be questioned.